Sizing strategy of on–off and modulating heat pump systems based on annual energy analysis. (May 2016) - Bagarella, G.; Lazzarin, R.; Noro, M.
Highlights: Annual behaviors of both on–off and variable capacity heat pumps were simulated. The higher the modulation the higher the advantages of the variable capacity system. These advantages strongly depend on the sizing of both the on–off unit and tank. Cycling losses cannot be neglected when evaluating heat pump annual performance. Abstract: In recent years the use of high efficient variable speed heat pumps has spread widely. Though several studies were carried out in the past comparing on–off and modulating strategies in heat pump units, only few works considered the whole heat pump system. Moreover, because of lack of knowledge about cycling losses, most of comparisons between modulating and on–off strategies did not consider the effects of the reduced coefficient of performance of a system at start-up. In this work simulations were carried out considering both on–off and modulating air-to-water heat pump systems in a single family house located in Italy. The aim of this study is to evaluate how the heat pump sizing, the thermal storage sizing and the cycling losses phenomenon can influence the annual energy performance of both the systems (on–off and modulating) and to investigate when modulating heat pump plants are actually more efficient than on–off.